Local forest structure variability increases resilience to wildfire in dry western U.S. coniferous forests - Koontz, Michael J.; North, Malcolm P.; Werner, Chhaya M.; Fick, Stephen E.; Latimer, Andrew M.; Swenson, Nathan (Ecology letters, 2020)
A ‘resilient’ forest endures disturbance and is likely to persist. Resilience to wildfire may arise from feedback between fire behaviour and forest structure in dry forest systems. Frequent fire creates fine‐scale variability in forest structure, which may then interrupt fuel continuity and prevent future fires from killing overstorey trees. Testing the generality and scale of this phenomenon is challenging for vast, long‐lived forest ecosystems. We quantify forest structural variability and fire severity across >30 years and >1000 wildfires in California's Sierra Nevada. We find that greater variability in forest structure increases resilience by reducing rates of fire‐induced tree mortality and that the scale of this effect is local, manifesting at the smallest spatial extent of forest structure tested (90 × 90 m). Resilience of these forests is likely compromised by structural homogenisation from a century of fire suppression, but could be restored with management that increases forest structural variability. Structurally variable forests may be more likely to persist in the face of wildfire disturbance, but demonstrating this phenomenon at an ecosystem‐scale is challenging. We linked local forest structural heterogeneity to wildfire severity for over 1000 fires across a 34‐year period in the Sierra Nevada mountain range and found that greater heterogeneity strongly reduced the probability of complete tree mortality. The local‐scale effect of forest structure on fire effects feeds back to maintain landscape heterogeneity, promoting forest resilience on an ecosystem‐scale.